2014
DOI: 10.1111/acer.12365
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Sustained Binge Drinking in Young Adults

Abstract: The determinants of sustained binge drinking are similar to predictors of binge drinking reported in the literature. Early identification of, and intervention with, youth who are impulsive, inclined toward novelty seeking, and who report higher levels of early sub clinical depressive symptoms might forestall their involvement in risky alcohol use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 38 publications
5
34
0
Order By: Relevance
“…The association could be attributed to the fact that university students who report strong religious affiliation are more likely to be invested in religions that preach abstention from alcohol or moderation in its consumption, coupled with the higher levels of religious faith reported in the present sample by females than by males (t = 2.05, p < .05). The relationship between impulsivity and binge drinking was also only partially consistent with previous results in the Canadian literature (e.g., Carlson et al, 2010;Wellman et al, 2014), in that high levels of impulsivity were associated with binge drinking, but for females only. Explanations for such a relationship are largely based on neurological differences, with more impulsive people tending to exhibit less control over heavy alcohol use and less foresight regarding the consequences of consuming large amounts of alcohol.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The association could be attributed to the fact that university students who report strong religious affiliation are more likely to be invested in religions that preach abstention from alcohol or moderation in its consumption, coupled with the higher levels of religious faith reported in the present sample by females than by males (t = 2.05, p < .05). The relationship between impulsivity and binge drinking was also only partially consistent with previous results in the Canadian literature (e.g., Carlson et al, 2010;Wellman et al, 2014), in that high levels of impulsivity were associated with binge drinking, but for females only. Explanations for such a relationship are largely based on neurological differences, with more impulsive people tending to exhibit less control over heavy alcohol use and less foresight regarding the consequences of consuming large amounts of alcohol.…”
Section: Discussionsupporting
confidence: 88%
“…One personality trait that has been consistently correlated with binge drinking in the literature, especially among college students, is impulsivity (Balodis et al, 2009;Carlson et al, 2010;Caswell, Celio, Morgan, & Duka, 2016;Clark et al, 2012;Townshend, Kambouropoulos, Griffin, Hunt, & Milani, 2014;Wellman, Contreras, Dugas, O'Loughlin, & O'Loughlin, 2014). In the literature, impulsivity is considered a multifaceted concept (as noted in Caswell et al, 2016); however, most commonly impulsivity refers to a deficits in the ability to regulate present actions and plan proactively, or to favouring spontaneous behaviour over regard for future consequences.…”
Section: Impulsivitymentioning
confidence: 99%
“…Consistent with this find ing, the academic expectation and aspira tion variables had relatively weaker correlations with the indicators of aca demic engagement and performance. Whether the disengagement and poor per formance prevents students from achiev ing their educational goals may depend on whether binge drinking is sustained, 42 supporting the need for early intervention efforts targeting heavy alcohol users.…”
Section: Discussionmentioning
confidence: 99%
“…Our study adds to these other studies by investigating both current and past drinking and by focusing specifically on binge drinking in young adults. We previously reported that 85% of NDIT participants who binged at age 20 years sustained that behavior until at least age 24 years [25]. Although binge and heavy drinking generally decrease with age [10,12], a review of six longitudinal studies conducted in the United States, Britain, and Finland found that drinking patterns in early adulthood were strong predictors of both frequency of alcohol use and problem drinking at ages 30 and 48 years [36].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous NDIT study, drinking alcoholic beverages at least once per month in three or more years during high school predicted the likelihood of sustaining binge drinking between age 20 and 24 years [25]. Alcohol consumption was assessed in each of the 20 survey cycles during high school with the question "During the past three months, how often did you drink alcohol (beer, wine, hard liquor)?"…”
Section: Study Variablesmentioning
confidence: 99%